When memory is the apple of discord: May 13, 2020, and the Palmares Foundation - Lopes, Juliana Serzedello Crespim; Sergio da Costa Neves, Paulo (Revista de História, 2022)
This paper reflects on the political disputes around the memory of slavery and its abolition in Brazil, analyzing the publications made on the website and the official social media of the Fundação Cultural Palmares (FCP) in May 2020. In these texts, the FCP, led by Sérgio Camargo, seeks to reiterate the legacy of Princess Isabel as the author of abolition and denounce the mythological character of Zumbi dos Palmares. The consolidation of “places of memory” (NORA, 1993) is neither a natural nor an inexorable consequence of historical processes, but the result of social and symbolic conflicts and disputes (LE GOFF, 1990). In this regard, this article investigates the symbolic and historical elements mobilized by the current FCP management to disqualify and dismantle the recent racial equality policies based on the reconstruction of symbols, heroes, and ephemeris of Blackness which emerged following redemocratization in the 1980s.